(untitled) (Research, Society and Development, 2023)
Since the beginning of the COVID-19 pandemic in December 2019, many infected patients have reported changes in taste and smell as early symptoms. The dentist must be able to diagnose this symptom and refer the patient to specialized health services. This study aimed to carry out a narrative review on the possible physiopathology of dysgeusia and ageusia in patients infected with SARS-CoV-2. Data were collected from studies identified in the VHL, Google Scholar, LILACS, PubMed, SciELO and Web of Science databases, using as descriptors: dysgeusia, ageusia, pathophysiology and coronavirus. Among the possible mechanisms for dysgeusia, stand out the viral invasion into nervous tissue, secondary to olfactory alterations, relation with comorbidities and drugs, association with the great presence of the virus in saliva and its high affinity for several angiotensin-2 enzyme receptors present in the oral cavity. Therefore, taste changes are typical symptoms in patients infected with SARS-CoV-2 and who tend to regress over time. However, its pathophysiology, action mechanism and prognosis are still not well established, requiring further experimental studies.